Development of student worksheet on growth and development of drought-stressed plants - Saifullah Mamonto; Novri Youla Kandowangko; Frida Maryati Yusuf (Assimilation: Indonesian Journal of Biology Education, 2023)
This study aimed to determine the validity, practicality, and effectiveness of developing student worksheets on the growth and development of drought-stressed plant material. The subjects of this study were students of 12th grade Science 1 of Senior High School 1 Tapa. The worksheet development used the ADDIE development model. The instruments used were Validation Sheets, Learning Implementation, Student Activities, Student Response Questionnaires, and THB questions. Student worksheet based on drought stressed plant study of growth and development material has met the valid, practical and effective categories. Based on the results obtained from the validation and trial of products on a limited scale, the development of student worksheets on the growth and development of drought-stressed plant material is suitable to be used for learning, as well as practical, and can improve student learning outcomes.